Prospective observational study of baloxavir marboxil in adults and adolescents with uncomplicated influenza from China - Liao, Guichan; Xia, Muye; Jiang, Yuanhui; Chen, Hongjie; Liao, Wei; Peng, Jie; Cai, Shaohang (Frontiers in Microbiology, 2023)
There are limited data on the efficacy of baloxavir marboxil (baloxavir) versus oseltamivir in Chinese patients with influenza A. This is an observational, real-world study involving 246 patients (baloxavir, n = 147, oseltamivir, n = 99) who were tested positive for influenza A. Baloxavir or oseltamivir antiviral treatment was decided by the clinician along with the patient. No significant differences were observed in demographic data between the two groups. The duration of fever was significantly shorter in the baloxavir group (P < 0.001). However, the duration of symptoms was not significant different (P = 0.167). Multivariable Cox analysis showed the independent factors affecting duration of fever were baloxavir treatment (HR=2.033, P < 0.001), fever on day 1 (HR=0.741, P = 0.010) and CRP level (HR=1.009, P = 0.039). Moreover, sex (HR=0.660, P = 0.019) and monocyte count (HR = 1.355, P = 0.018) were independent factors affecting the duration of symptoms. No significant difference in change of health-related quality of life (P > 0.05), positive rate of viral antigen on day 3 (P = 0.477) between the two groups. Remarkably, a mutation was observed in one case on the third-day after baloxavir treatment compared with first-day, from cysteine to serine at position 384 of the PA subunit. In summary, with comparable clinical benefits to oseltamivir, baloxavir was proven an effective anti-viral therapy in Chinese patients with influenza in the clinical setting.